The crystal structure of bis(μ2-5-chloro-2-oxido-N-(1-oxidopropylidene)benzohydrazonato-κ5 N,O,O′:N′,O′′)-octakis(pyridine-κ1 N)trinickel(II) C60H56Cl2N12Ni3O6 - Xin Wang; Liguo Yang; Yizhuo Dong; Yanlin Ye; Yifan Wang (Zeitschrift für Kristallographie - New Crystal Structures)
C60H56Cl2N12Ni3O6, triclinic, P1‾ $P\overline{1}$ (no. 2), a = 12.684(5) Å, b = 12.827(5) Å, c = 19.100(7) Å, α = 84.641(4)°, β = 81.178(4)°, γ = 85.471(4)°, V = 3050.7(19) Å3, Z = 2, R gt(F) = 0.0267, wR ref(F 2) = 0.0735, T = 298 K.